A Norma de Desempenho como orientação para a elaboração do Código de Obras de Santana do Livramento - RS. - Nicolini, Elda (2015)
The ABNT NBR 15575 - Performance - Buildings, came into force in July 2013, bringing major changes to the Construction sector, because it establishes minimum quality standards, based on the performance and durability of the systems. The focus of this Standard is on the requirements of users for the housing building and its systems, as their behavior in use and not in limitation of how systems are built. On the other hand, the Code of Constructions and Buildings in the city of Santana do Livramento (COE-SL), RS, is being reworked by the City Hall and it is necessary to include articles in this Act that address the performance requirements. The overall objective of the research was to conduct a thorough study of the Standard and verify what are the main requirements that should guide the Code of Constructions and Buildings in the city, which have been facing serious problems due to climatic factors (such as rainfall and strong winds). There was, after literature review on standardization, performance, municipal building codes, and especially on the Performance Standard, verification of each of the standard requirements and were prepared tables of systems addressed to the verification of need, or not, its inclusion in the COE-SL. Thus, in the presentation of the results, we defined how each selected item might be required and how to do this requirement. Thus, we sought to contribute to transform the Code of Constructions and Buildings in an efficient mechanism in the process of obtaining buildings with good performance.